Effectiveness of Malaria Eradication Programs in Endemic Areas: A Case Study in Papua province - Kasman Lestaluhu; Olyvia Rosalia (Journal of Public Health Indonesian, 2025)
This study aims to evaluate the effectiveness of malaria eradication programs in Papua, Indonesia, with a focus on implementation in endemic areas. Through a qualitative approach and case study method, the study involved in-depth interviews with health workers, communities, and policy makers in several districts in Papua. The results showed that although programs such as the distribution of insecticide-treated mosquito nets and spraying of insecticides have had a positive impact in the reduction of malaria cases, significant challenges remain, especially regarding the accessibility of remote areas and limited resources. Communities and health workers expect an increase in malaria education, training for field workers, and increased budgets and equipment to support the success of the program throughout Papua. This study provides recommendations to improve coordination between sectors and the implementation of programs that are more targeted and based on local needs.